2011
DOI: 10.1016/j.clinph.2011.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Contact size does not affect high frequency oscillation detection in intracerebral EEG recordings in a rat epilepsy model

Abstract: Objective-High frequency oscillations (HFOs) have been implicated in ictogenesis and epileptogenesis. The effect of contact size (in the clinical range: 1-10 mm 2 ) on HFO detection has not been determined. This study assesses the feasibility of HFO detection in a rat epilepsy model using macrocontacts and clinical amplifiers, and the effect of contact size on HFO detection within the macrocontact range.Methods-Eight epileptic rats were implanted with intracerebral electrodes containing three adjacent contacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
3
25
1
1
Order By: Relevance
“…One study found a significant reduction in the number of fast ripple-frequency HFOs recorded with standard clinical electrodes (surface area 9.4 mm 2 ) compared with microelectrodes [65]. In contrast, other experiments compared hippocampal ripple-and fast ripplefrequency HFOs recorded with electrodes of different contact sizes in epileptic rats and found no difference in HFO duration or spectral frequency with respect to electrode diameter, although the mean amplitude of all HFOs was significantly lower compared with the amplitude of HFOs recorded with microelectrodes [4,66]. In subsequent work involving patients from this same group, similar rates of HFOs were found among electrodes with surface areas between 0.2 and 5 mm 2 [67], suggesting that smaller contact diameter would not necessarily improve the detection of HFOs.…”
Section: Recording Detection and Quantification Of Spontaneous Hfosmentioning
confidence: 81%
See 1 more Smart Citation
“…One study found a significant reduction in the number of fast ripple-frequency HFOs recorded with standard clinical electrodes (surface area 9.4 mm 2 ) compared with microelectrodes [65]. In contrast, other experiments compared hippocampal ripple-and fast ripplefrequency HFOs recorded with electrodes of different contact sizes in epileptic rats and found no difference in HFO duration or spectral frequency with respect to electrode diameter, although the mean amplitude of all HFOs was significantly lower compared with the amplitude of HFOs recorded with microelectrodes [4,66]. In subsequent work involving patients from this same group, similar rates of HFOs were found among electrodes with surface areas between 0.2 and 5 mm 2 [67], suggesting that smaller contact diameter would not necessarily improve the detection of HFOs.…”
Section: Recording Detection and Quantification Of Spontaneous Hfosmentioning
confidence: 81%
“…For example, ripple-and fast ripple-frequency HFOs could be recorded using clinical macroelectrode, and the volume of tissue and/or spatial distribution associated with fast-ripple frequency HFOs was larger than predicted from microelectrode recordings [65,66,100]. The link between the rates of fast ripple-frequency HFOs and SOZ was also confirmed [65,101,102], and from these studies evidence for the association of ripple-frequency HFOs and the SOZ in MTLE and neocortical epilepsies was obtained, although fast ripple-frequency HFOs appear more specific to the SOZ, particularly in MTLE [63].…”
Section: Interictal Hfosmentioning
confidence: 99%
“…Wie bereits erwähnt, kann zum momentanen Zeitpunkt nicht gesagt werden, ob die Elektrodengröße und Aufzeichnungsmethode einen entscheidenden Einfluss darauf hat, dass HFO zuverlässig aufgezeichnet werden können [12,40]. [15].…”
Section: Bestehendemethodische Herausforderungenunclassified
“…Four stainless steel screws (2.4 mm length) were fixed to the skull and 4 small holes were drilled to allow the implantation of bipolar electrodes (20-30 k ; 30-50 mm length; distance between exposed tips: 500 m) made by twisting and glueing two 0.1524 mm resin-insulated copper wires. Contacts consisted of the cut edge of the wire (0.018 mm 2 ) (Châtillon et al, 2011). Electrodes were implanted in the CA3 subfield of the ventral hippocampus (AP: −4.4, ML: ±4, DV: −8.8), medial entorhinal cortex (AP: −6.6, ML: ±4, DV: −8.8), ventral subiculum (AP: −6.8, ML: ±4, DV: −6) and dentate gyrus (AP: −4.4, ML: ±2.4, DV: 3.4).…”
Section: Animal Preparationmentioning
confidence: 99%